Farmers’ perceptions, awareness, attitudes and adaption behaviour towards climate change - Akhtar, Rulia; Afroza, Rafia; Masud, Muhammad Mehedi; Rahman, Mahfuzur; Khalid, Haniza; Duasa, Jarita (Taylor & Francis, 2018)
Using responses from a questionnaire survey conducted on a sample of 400 rice farmers from Kedah in Malaysia, this article examines rice farmers’ perception, awareness, attitudes and adaptation behaviours towards mitigating climate change. The data collected was analysed using structural equation modelling. The findings of this study show that 84% of the respondents perceive a decrease in rainfall, while 75% perceive an increase in temperature over the last 10–15 years due to climate change. The study also finds a significant and positive association between farmers’ perception of climate change, awareness (AWN), attitudes (ATT) and adaptation behaviour (ADB). Furthermore, the results reveal that awareness and attitudes play a mediating role between perception and adaptation behaviour. The findings could be useful to public and private organizations in learning more about farmers’ perceptions and adaptation behaviour in developing a policy framework to reduce adverse effects of climate change.